Kekerasan terhadap Tokoh Utama dalam Novel Kerumunan Terakhir Karya Okky Madasari: Penelitian - Malipi, Rahmawaty; Didipu, Herman; Sartika, Eka (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Literary works are a reflection of reality processed through the author's imagination and act as a medium to convey life values. Okky Madasari's novel Kerumunan Terakhir presents a portrait of social and family problems in the context of changing times and the dominance of social media. This study aims to explain the reflection of violence against the main character in the novel. This study uses a descriptive qualitative approach by analyzing words, actions, and interactions between characters to reveal the forms and backgrounds of the violence that occurs. The results of the study show that the character Jayanegara experiences violence due to his disappointment with his father figure who does not set an example, often lies, and has affairs. This inner conflict gives rise to retaliatory actions in the form of open criticism on social media, which culminates in physical violence from the father. Through this novel, readers are invited to understand the importance of the role of parents in shaping children's character and the psychological impact of failed communication and role models in the family.